Tribotechnical properties of coatings based on magnesium compounds - Shchepetov, V.V.; Fialko, N.M.; Bys, S.S. (Problems of Tribology, 2025)
The article summarizes the results of studies of tribotechnical properties of detonation coatings based on magnesium orthosilicate under conditions of constant load in the sliding velocity field. The structural and phase composition of the coatings was studied using modern physical analysis methods. The developed and studied coatings based on magnesium orthosilicate have high and stable antifriction properties in the entire load-velocity range of tests. It is emphasized that the result of antifriction under friction conditions is the additive effect of both the carbide graphite film and dispersed surface oxide structures, the synthesis of which provides modification of the surface of the structure, which is capable of self-lubrication and at the same time limits the development of unacceptable destruction processes